Reliability of Radiographic Assessments of Adolescent Midshaft Clavicle Fractures by the FACTS Multicenter Study Group. Issue 9 (September 2017) - Li, Ying; Donohue, Kyna S.; Robbins, Christopher B.; Pennock, Andrew T.; Ellis, Henry B.; Nepple, Jeffrey J.; Pandya, Nirav; Spence, David D.; Willimon, Samuel Clifton; Heyworth, Benton E.
Abstract : Objectives: There is a recent trend toward increased surgical treatment of displaced midshaft clavicle fractures in adolescents. The primary purpose of this study was to evaluate the intrarater and interrater reliability of clavicle fracture classification systems and measurements of displacement, shortening, and angulation in adolescents. The secondary purpose was to compare 2 different measurement methods for fracture shortening. Methods: This study was performed by a multicenter study group conducting a prospective, comparative, observational cohort study of adolescent clavicle fractures. Eight raters evaluated 24 deidentified anteroposterior clavicle radiographs selected from patients 10–18 years of age with midshaft clavicle fractures. Two clavicle fracture classification systems were used, and 2 measurements for shortening, 1 measurement for superior–inferior displacement, and 2 measurements for fracture angulation were performed. A minimum of 2 weeks after the first round, the process was repeated. Intraclass correlation coefficients were calculated. Results: Good to excellent intrarater and interrater agreement was achieved for the descriptive classification system of fracture displacement, direction of angulation, presence of comminution, and all continuous variables, including both measurements of shortening, superior–inferior displacement, and degrees of angulation. Moderate agreement was achieved for the Arbeitsgemeinschaft für Osteosynthesefragen classification system overall. Mean shortening by 2 different methods were significantly different from each other ( P < 0.0001). Conclusions: Most radiographic measurements performed by investigators in a multicenter, prospective cohort study of adolescent clavicle fractures demonstrated good-to-excellent intrarater and interrater reliability. Future consensus on the most accurate and clinically appropriate measurement method for fracture shortening is critical.